(untitled) (Research, Society and Development, 2022)
Studies in the field of work are generally conducted with employees who are not in leadership positions, making important investigations that include leaders and with an emphasis on promoting positive and virtuous actions. The main objective of this study was to analyze the relationships between character strengths and leadership styles. 150 business leaders from companies in São Paulo and Minas Gerais participated, 54.7% of whom were male and worked in the function for an average period of 9.47 years. As instruments, a demographic questionnaire, the Escala de Forças de Caráter and the Escala de Avaliação do Estilo Gerencial were used. The results indicated that the character strengths were more correlated to the relationship factor. In addition, through path analysis, the character strenghts explained positively the relationship factor and negatively the task factor of managerial styles. The results are discussed in light of the literature and give indications of how character strengths can be used in interventions with leaders.